PELATIHAN KEWIRAUSAHAAN BERBASIS DIGITAL MARKETING DIDESA SUKABUMI UNTUK MENGHADAPI ERA EKONOMI DIGITAL - Tya Rahmawati; Indah Setiyani; Dhea Putri Fellisa; Artha Puspa Agtni; Nur Alfiyatul Mukaromah; Unna Ria Safitri (KRIDA CENDEKIA, 2025)
In this era, digital technology and information are very necessary to keep up with existing developments in order to continue the ongoing business. The current choice that is easy to access and reach the wider community is digital marketing. This community service aims to improve the skills and understanding of MSME actors in Sukabumi Village, Boyolali, Central Java, who still apply traditional marketing and have not optimally utilized digital technology and information. Through community service activities in the form of surveys, socialization, training, participants are explained about digital entrepreneurship, how to create and manage business accounts on social media and the use of graphic design tools and applications. The results of the socialization and training show an increase in the understanding and skills of MSME actors in utilizing digital marketing to promote their products. This community service provides real involvement to help MSME actors adapt to the digital era, this activity also encourages business changes towards a more modern and competitive business style.